Electrochemical preparation of Nb2O5 nanochannel photoelectrodes for enhanced photoelectrocatalytic performance in removal of RR120 dye - Khan, Saad Ullah [UNESP]; Perini, João Angelo Lima [UNESP]; Hussain, Sajjad; Khan, Hammad; Khan, Sabir [UNESP]; Boldrin Zanoni, Maria V. [UNESP] (Elsevier, 2020)
The present work describes the synthesis of niobium oxide nanochannels (Nb2O5NCs) with high surface area, porosity, photocurrent density, and photoelectrochemical stability as photocatalyst. The Nb2O5NCs were prepared by electrochemical anodization of niobium foil in different electrolytes: 1 M H2SO4 containing 0.4 wt% HF (S1); glycerol containing 0.4 M NH4F (S2); 0.25 g NH4F with 4 vol% water in glycol at 50 °C (S3); and glycerol containing 10 wt% K2HPO4, at 130 °C (S4, annealed in air; S5, annealed in N2). All the Nb2O5NCs showed well-organized arrays of nanochannels grown on the Nb foil, with tube diameters in the order S4<S2<S1<S3 and film thicknesses in the order S1<S2<S3<S4, as determined using FEG-SEM analyses. The samples were also characterized using XRD, EDX, DRS, XPS, EIS, Mott-Schottky analysis, and LSV curves. But, best results were obtained only when phosphorus (about 1% doping) was incorporated into the electrodes samples prepared in glycerol containing 10 wt% K2HPO4 at 130 °C (i.e. S4 and S5). This procedure enhances the absorption intensity in the UV–Vis regions, the conductivity, the charge carrier density, and the photocurrent density. The Nb2O5NC sample S5 was tested for the degradation of Procion Red HE-3B (RR120) dye, as a model pollutant, achieving efficient photoelectrodegradation with nearly 2 times higher mineralization efficiency compared to photolysis (PT) and photocatalysis (PC). Thus, the results indicate that the modification of Nb2O5NC thin film photoelectrodes by phosphorous doping can be a powerful and efficient alternative to usual approaches applied to the treatment of complex reactive dyes.
Keywords: Characterization; Nb2O5 nanochannels; Photoelectrocatalysis; RR120 degradation; Synthesis